Efficacy and Tolerability of Two Different Low-Volume Split-Dose Polyethylene Glycol Electrolytes Solution Bowel Preparation for Morning Colonoscopy - Hefeng Tian; Hui Li; Xuanrui Zhu; Wenlong Liu; Ying Fan; Lei Shi; Xiu Wang (Canadian Journal of Gastroenterology and Hepatology)
Object. The study compared the efficacy and tolerability of two different low-volume split-dose polyethylene glycol electrolytes solution (PEG-ELS) bowel preparation for morning colonoscopy. Methods. A total of 120 patients were randomized to receive either the control group (n = 64) or the experimental group (n = 65). Patients in the control group adopted the low-volume split-dose regimen one, and patients in the experimental group adopted the low-volume split-dose regimen two. Those randomized to regimen one were instructed to take 0.75 L PEG two hours after dinner the day before the colonoscopy and 1.5 L PEG 4 hours before the colonoscopy. Patients assigned to regimen two were invited to consume 1.5 L PEG two hours after dinner the day before the colonoscopy and 0.75 L PEG 4 hours before the colonoscopy. The quality of bowel preparation, rated according to a Boston Bowel Preparation Scale (BBPS), represented the primary outcome measure. Tolerability, satisfaction, and lesions detection rated were secondary outcomes. Results. There was no significant difference between the transverse colon and right colon scores between the two groups (P>0.05). The low-volume split-dose regimen two showed a higher success rate for cleansing of the right colon and overall colon (P<0.05). For the comparison of the patients’ bowel tolerance, there were no statistical differences between the two groups regarding thirst, abdominal pain or abdominal discomfort, abdominal distension, dizziness or headache, anal discomfort, and sleep disturbance (P>0.05). However, regimen two had significantly less nausea, vomiting, and fatigue than regimen one (24.62% vs. 42.19%, P=0.034; 10.77% vs. 25.00%, P=0.035; 6.15% vs. 21.88%, P=0.010, respectively). Patient-reported satisfaction and willingness to repeat the bowel preparation were significantly higher for low-volume split-dose regimen two than for low-volume split-dose regimen one (P=0.011; P=0.015). Conclusions. In early morning colonoscopies, the bowel-cleansing efficacy and patient tolerability of low-volume split-dose regimen two were superior to low-volume split-dose regimen one.